Bumblebee colony density on farmland is influenced by late‐summer nectar supply and garden cover. Issue 5 (15th January 2021) - Timberlake, Thomas P.; Vaughan, Ian P.; Baude, Mathilde; Memmott, Jane
Abstract: Floral resources are important in limiting pollinator populations, but they are often highly variable across time and space and the effect of this variation on pollinator population dynamics is not well understood. The phenology (timing) of floral resources is thought to be important in structuring pollinator populations, but few studies have directly investigated this. Our study quantifies the landscape composition, seasonal nectar and pollen supply and Bombus terrestris colony density of 12 farms in southwest UK to investigate how landscape composition influences the phenology of floral resources and how both these factors affect colony density. We use this information in a spatially explicit predictive model to estimate the effect of different farmland management scenarios on seasonal resource supplies and colony density. We find that farmland nectar supply during September is a strong predictor of B. terrestris colony density in the following year, explaining over half of all the variation in colony density; no other period of resource availability showed a significant association. Semi‐natural habitat cover was not a good proxy for nectar or pollen supply and showed no significant association with colony density. However, the proportional cover of gardens in the landscape was significantly associated with colony density. The predictive model results suggest that increasing the area of semi‐natural flowering habitat has limited effect on bumblebee populations. However, improving the quality of these habitats through Environmental Stewardship and other management options is predicted to reduce the late‐summer resource bottleneck and increase colony density. Synthesis and Applications . Our study demonstrates the importance of considering the phenology of resources, rather than just total resource availability, when designing measures to support pollinators. Late summer appears to be a resource bottleneck for bumblebees in UK farmland, and consequently management strategies which increase late‐summer nectar availability may be the most effective. These include mowing regimes to delay flowering of field margins until September, planting late‐flowering cover crops such as red clover and supporting late‐flowering wild plant species such as Hedera helix . Our results also suggest that rural gardens may play an important role in supporting farmland bumblebee populations. Abstract : Our study demonstrates the importance of considering the phenology of resources, rather than just total resource availability, when designing measures to support pollinators. Late summer appears to be a resource bottleneck for bumblebees in UK farmland, and consequently management strategies which increase late‐summer nectar availability may be the most effective. These include mowing regimes to delay flowering of field margins until September, planting late‐flowering cover crops such as red clover and supporting late‐flowering wild plant species such as Hedera helix . Our results also suggest that rural gardens may play an important role in supporting farmland bumblebee populations.